Alternautas in The Changing Landscape of Latin America’s and Global Development Imaginaries (Alternautas, 2022)
First off, a very warm welcome to this landmark issue of Alternautas, now hosted in an OJS platform at the University of Warwick. Opening our first issue as an OJS journal is a significant milestone and in this editorial introduction we would like to share with you, our dear readers, some insights about our journey so far. Alternautas collective editorial project has been one of the pioneers in the creation of decentralized and collaborative media platforms for the production and dissemination of non-mainstream academic and activist knowledge.